The Effect of Dopamine Antagonist Treatment on Auditory Verbal Hallucinations in Healthy Individuals Is Clearly Influenced by COMT Genotype and Accompanied by Corresponding Brain Structural and Functional Alterations: An Artificially Controlled Pilot Study - Zhuo, Chuanjun; Xu, Yong; Zhang, Li; Jing, Rixing; Zhou, Chunhua (Frontiers in Genetics, 2019)
Few studies have been conducted to explore the influence of the catechol-o-methyltransferase (COMT) genotype on the severity of and treatment efficacy on auditory verbal hallucination (AVH) symptoms in healthy individuals with AVHs (Hi-AVHs). We hypothesized that the efficacy of dopamine antagonist treatment on AVHs in Hi-AVHs may be influenced by their COMT genotype and may be accompanied by corresponding brain alterations. To preliminarily investigate and test our hypothesis in an artificially controlled pilot study, we enrolled 42 Hi-AVHs as subjects and used magnetic resonance imaging and genetic methods to explore the basis brain features to investigate whether the efficacy of dopamine antagonist treatment on AVHs in Hi-AVH subjects was influenced by their COMT genotype or not. We found that COMT-met genotype subjects’ treatment response was better than that of COMT-val subjects. Although COMT-met genotype subjects demonstrated an increase in global functional connectivity density (gFCD) but no difference on gray matter volume (GMV) compared to COMT-val genotype subjects at baseline, notably, we found that both groups demonstrated gFCD and GMV reduction after treatment, but the reduction was more widespread in COMT-met genotype subjects than in COMT-val genotype subjects. This is the first study to report that Hi-AVH subjects’ baseline brain functional features are influenced by their COMT genotypes and that the COMT-met genotype subjects exhibit better responses to dopamine antagonists but have more widespread GMV and gFCD reduction than subjects with the COMT-val genotype. Despite several limitations, these findings may provide auxiliary information to further explain the mechanisms of AVHs and provide a clue for scholars to further explore specific treatment targets for AVHs in Hi-AVH subjects or in schizophrenia patients.